2007
DOI: 10.1128/mcb.00342-07
|View full text |Cite
|
Sign up to set email alerts
|

Bmp2 Is Critical for the Murine Uterine Decidual Response

Abstract: The process of implantation, necessary for all viviparous birth, consists of tightly regulated events, including apposition of the blastocyst, attachment to the uterine lumen, and differentiation of the uterine stroma. In rodents and primates the uterine stroma undergoes a process called decidualization. Decidualization, the process by which the uterine endometrial stroma proliferates and differentiates into large epithelioid decidual cells, is critical to the establishment of fetal-maternal communication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
330
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 317 publications
(342 citation statements)
references
References 72 publications
9
330
0
3
Order By: Relevance
“…We also found that downstream of LPA 3 , Bmp2/Wnt4 signaling (Table 2 and Fig 4A) was activated. Bmp2 and Wnt4 are well‐known decidual factors acting downstream of HB‐EGF signaling (Paria et al , 2001; Lee et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Interestingly, a significant negative correlation of gene expression profiles was observed between T13‐injected uteri and uteri null for either Egfr (a target of HB‐EGF), Bmp2, and Wnt4 (Large et al , 2014; Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that downstream of LPA 3 , Bmp2/Wnt4 signaling (Table 2 and Fig 4A) was activated. Bmp2 and Wnt4 are well‐known decidual factors acting downstream of HB‐EGF signaling (Paria et al , 2001; Lee et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Interestingly, a significant negative correlation of gene expression profiles was observed between T13‐injected uteri and uteri null for either Egfr (a target of HB‐EGF), Bmp2, and Wnt4 (Large et al , 2014; Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The raw data of uterine‐specific Egfr or Wnt4 KO were kindly disclosed by the corresponding author of the previous article (Large et al , 2014). The data of Bmp2 (Lee et al , 2007; accession no. GSE10193), Egfr, or Wnt4 KO were analyzed using R (https://www.R-project.org/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast, the stimulated horn of the uterine GR KO mice showed no significant increase in uterine size compared with the unstimulated horn. Previous studies have determined molecular markers of decidualization, including induction of the genes bone morphogenetic protein 2 (Bmp2) and wingless-related MMTV integration site 4 (Wnt4) (10,11). The expression of Bmp2 and Wnt4 mRNA was highly induced in the decidual horn of the control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the expressions of BMP2 and Wnt4, which were induced during stromal decidualization in the mouse, were conserved in the human stromal cells undergoing decidualization [52]. Studies reveal that Wnt4 is not the only Wnt ligand that is associated with BMP2, since BMP2 was shown to be responsible for the upregulation of Wnt6 of murines [53]. Wnt6 was shown to be expressed in proliferating stromal cells of mice during post-implantation uterine development.…”
Section: Uterus In Implantation Period: Decidualizationmentioning
confidence: 99%